Automated surveillance in French ICUs: is it feasible? Results from a survey in French ICUs participating in a surveillance network. (September 2021) - Lepape, A.; Machut, A.; Gerbier-Colomban, S.; Kuczewski, E.; Rasigade, J-P.; Timsit, J-F.; Vanhems, P.; Wallet, F.; Savey, A.; Friggeri, A.; ,
Summary: A survey was undertaken to evaluate the level of computerization in intensive care units (ICUs) within a French network dedicated to the surveillance of healthcare-associated infections, antimicrobial use (AMU) and antimicrobial resistance (AMR) in ICUs (REA-REZO). Ninety-eight ICUs responded, and patient records were computerized in 57%, antimicrobial prescriptions were computerized in 59% and AMR epidemiology was computerized in 72%. AMU and AMR feedback was provided to the ICU itself for 77% and 65% of ICUs, respectively, and feedback was provided to the national surveillance for 79% and 65% of ICUs, respectively. This study suggests that the level of computerization in ICUs requires further improvement.